Teknik Fault Tolerance Untuk Sensor Jaringan Wireless - N. Suruali (Industrial Engineering Study Program, Pattimura University, 2012)
Networking embeded sensor is a nodes system with sensing, actuating, computation, communication, and storage resources facilities designed to yield a lower exploitation cost and a reliable tollerance fault technique. Problem is how to design this a backup fault tolerance of this sensor where every kind of resource can be replaced by others. At the beginning we propose a singgle spectrum which more wide than heterogeneous tollerance fault technique for networking sensor that consist of comuication and sensing and can support one another. After that, we shift to two specific approaches which one kind of sensor can back-up others. We assume the errors resulted from malfunction and high-level fault, and each technique has a different efficiency algorithm and effectivity.